2022
DOI: 10.20944/preprints202206.0424.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Associated Thrombotic Thrombocytopenic Purpura: A Case Report and Systematic Review

Abstract: Introduction: The proliferation of literature regarding COVID-19 pandemic has served to highlight a wide spectrum of disease manifestations and complications like thrombotic microangiopathies. Our review with a brief case presentation highlights the increasing recognition of TTP in COVID-19 and describes its salient characteristics. Methods: We screened the available literature in Pubmed, EMBASE and Cochrane database from inception till April 2022 of articles mentioning COVID-19 associated TTP in English Langu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…It has been reported that SARS-CoV-2 infection may be complicated by a variety of immunological phenomena, including thrombotic thrombocytopenic purpura (TTP), Guillain-Barre syndrome (GBS), and autoimmune hemolytic anemia (1)(2)(3)(4). Thrombotic thrombocytopenic purpura (TTP) is a thrombotic microangiopathy with high mortality.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that SARS-CoV-2 infection may be complicated by a variety of immunological phenomena, including thrombotic thrombocytopenic purpura (TTP), Guillain-Barre syndrome (GBS), and autoimmune hemolytic anemia (1)(2)(3)(4). Thrombotic thrombocytopenic purpura (TTP) is a thrombotic microangiopathy with high mortality.…”
Section: Introductionmentioning
confidence: 99%